Educational Leadership and Learning Quality: The Influence of the Princi-pal's Leadership Style on Teacher Performance - Puspitadani, Ersika; Yudea, Frans; Loo, Friskila (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
In the dynamic landscape of education, the role of school leadership is pivotal in shaping the experiences of both teachers and students. This research delves into the multifaceted relationship between the principal's leadership style, teacher performance, and learning quality. Through a combination of surveys, document analysis, and statistical analysis, this study explores the impact of various leadership styles on the educational environment. The findings underscore the profound influence of transformational leadership on teacher performance. Transformational leaders inspire and motivate teachers, fostering a collaborative and innovative atmosphere in which educators thrive. The positive correlation between transformational leadership and teacher performance contributes to improved learning quality, characterized by higher levels of student engagement, critical thinking, and academic achievement. Furthermore, the research recognizes the mediating role of school climate, emphasizing the significance of a positive and inclusive school environment in enhancing teacher motivation and job satisfaction. It also highlights potential challenges associated with laissez-faire and transactional leadership styles, emphasizing the need for support and long-term teacher commitment. This research expands our understanding of educational leadership theory and paves the way for the development of new theories that encompass the complex interplay between leadership styles, teacher performance, and learning quality. It offers a roadmap for transforming educational practices, policies, and theories to create a more dynamic, inclusive, and effective educational system. As the educational landscape continues to evolve, the findings of this research hold the potential to inspire change and innovation, ultimately shaping the future of education and enriching the lives of students and educators alike.